Practical tasks of studying literature in a foreign language and communication skills - Tatiana G. Bochina, Nadezhda V. Makrishina,; Karlygash S. Abylkhassova, Sholpan K. Zharkynbekova, Kuralay B. Urazayeva,; Petkova, Silviya (Opción, 2019)
The article is devoted to the methodology of teaching literature in a non-native language from the standpoint of developing students' skills of social experience via comparative qualitative research meth-ods. As a result, the method of studying literature in a non-native lan-guage causes different types of differentiation of tasks according to the degree of complexity for different groups of students. In conclusion, in the Kazakh school, the dominant role of speaking determines the role of the receptive mechanism, the important role of changing the speaker and listener, the wide involvement of audio recordings